Can the Urban Lifestyle Impact on Children BMI and Healthy Sleep? - Machado-Rodrigues, Aristides M.; Rodrigues, Daniela; Gama, Augusta; Nogueira, Helena; Fernandes, Helder Miguel; Stabelini Neto, António; Fernandes, Romulo [UNESP]; Padez, Cristina (Wiley, 2025)
Objectives: This study aimed to (i) compare children's lifestyle by urbanization level and (ii) examine the association between children's body mass index (BMI) and the risk of having unhealthy sleep (American Academy of Pediatrics). Methods: Eight thousand one hundred fifty-nine children (4124 females) aged 6–9 years were observed and classified as urban or nonurban. Height and weight were measured, and the BMI was calculated. Sleep habits, sedentary behaviors (i.e., TV viewing, computer and electronic games use), and active play were assessed by questionnaire. One-way analysis of covariances (ANCOVAs) and logistic regression analysis were used, with adjustments to potential confounders. Results: Urban males were significantly less active and spent more time in all sedentary activities than their nonurban peers during the week and the weekend. Urban girls spent significantly more time than their nonurban counterparts watching TV and playing electronic games. Furthermore, both urban and nonurban children with higher BMI had a relative higher risk of having unhealthy sleep duration. Conclusions: Findings revealed important associations between BMI and sleep duration in both urban and nonurban children. Place of residence has an important impact on weight status of this sample of children.
Keywords: health promotion; obesity; sedentary behavior; sleep guidelines; urbanization level